EVALUASI UJI IRITASI DAN UJI SIFAT FISIK SEDIAAN EMULGEL MINYAK ATSIRI BUNGA CENGKEH (Syzigium aromaticum) - Sari, Delia Komala; Sugihartini, Nining; Yuwono, Tedjo (Pharmaciana, 2015)
Inflammation is the human bodys response to a tissue damage as indicated by an increase of vascular permeability. One of the natural substances that can be used to treat inflammation is clove oil (MABC). This study aimed to evaluate the physical properties and MABC emulgel irritation test (Syzygium aromaticum). This experimental study was initiated by the emulgel formulation with three kinds of formula, with each formula contains MABC levels of 10% (F1), 12.5% (F2), and 15% (F3). The physical tests for emulgel was done including pH, spreading test and adhesive test and irritation test in guinea pigs using Draize test method. Statistical analysis by t test with a level of confidence 95% was conducted to detect a significant differences between the treatment groups. The emulgel formula with a concentration of 10%, 12.5% and 15% were physically stable, moreover the dispersive power test for each formula showed normal distribution data (p>0.05) and homogeneous (p>0.05), ANOVA test results obtained significantly different results in each formula (p<0.05), whereas the stickiness test results for each formula more than 30 minutes with pH 6. The results of irritation test by using Draize test Â method, indicated that each formula did not show any irritant effect.